Type-3/2 Seesaw Mechanism - Demir, Durmuş Ali; Demir, Durmuş Ali; Sargın, Ozan; Karahan, Canan; Sargın, Ozan (American Physical Society, 2021)
The type-I seesaw mechanism provides a natural explanation for tiny neutrino masses. The right-handed neutrino masses it requires are, however, too large to keep the Higgs boson mass at its measured value. We show that vector spinors, singlet leptons that are like right-handed neutrinos, generate tiny neutrino masses naturally through the exchange of spin-1/2 and spin-3/2 components. This one-step seesaw mechanism, which we call the type-3/2 seesaw, keeps the Higgs boson mass unchanged at one loop and gives cause therefore to no fine-tuning problem. If the on-shell vector spinor is a pure spin-3/2 particle, then it becomes a potential candidate for hidden dark matter which gets diluted due only to the expansion of the Universe. The type-3/2 seesaw provides a natural framework for the neutrino, Higgs boson, and dark matter sectors, with overall agreement with current experiments and observations.
Keywords: Neutrino masses; Higgs boson; Dark matter